1996
DOI: 10.1897/1551-5028(1996)015<1783:atsedf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Experimental Design for a Sediment Bioassay Using Growth of the Amphipod Hyalella Azteca for the Test End Point

Abstract: Abstract-We designed a sediment bioassay using 25% growth inhibition of Hyalella azteca as the end point. Hyalella azteca exhibits size-specific fecundity, so growth is a surrogate of reproductive production. We investigated density effects on growth to address whether crowding could affect test interpretation; amphipods in 14,000/m 2 exposures were 16 to 20% smaller than those at 7,000/m 2 . Using power analysis, we found that 20 to 25 samples are required to determine significance when ␣ ϭ 0.10 and 1 Ϫ ␤ ϭ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
11
0
3
Order By: Relevance
“…The present study demonstrated that the female amphipods were more sensitive than the males in terms of growth and that toxic effects could be neglected if both males and females were not used in the experiment or measured independently. In the natural environment, this delay in growth of female amphipods could consequently impair the reproduction of the population, because organisms need to reach a certain size before reproduction can occur [49] and larger organisms produce larger broods than smaller individuals [50]. A plausible explanation for this observation is the difference in response of female and male amphipods and the fact that they were not measured separately.…”
Section: Growthmentioning
confidence: 99%
“…The present study demonstrated that the female amphipods were more sensitive than the males in terms of growth and that toxic effects could be neglected if both males and females were not used in the experiment or measured independently. In the natural environment, this delay in growth of female amphipods could consequently impair the reproduction of the population, because organisms need to reach a certain size before reproduction can occur [49] and larger organisms produce larger broods than smaller individuals [50]. A plausible explanation for this observation is the difference in response of female and male amphipods and the fact that they were not measured separately.…”
Section: Growthmentioning
confidence: 99%
“…Kubitz et al [19] recommended a two-step process for assessing growth in sediment tests with H. azteca. A limited number of replicates are tested in a screening step and samples identified as possibly toxic are then tested in a confirmatory step with additional replicates.…”
Section: Relationship Between Growth and Reproduction Endpointsmentioning
confidence: 99%
“…Other investigators have reported measurement of growth in tests with H. azteca often provides unique information that can help to discriminate toxic effects of exposure to contaminants in sediment [19,47,52] or water [53][54][55]. Similarly, in sediment tests with the midge C. tentans, sublethal endpoints are often more sensitive than survival as indicators of contaminant stress [9,10,56].…”
Section: Relative Endpoint Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have reported measurement of growth in tests with H. azteca often provides unique information that can help to discriminate toxic effects of exposure to contaminants in sediment [19,47,52] or water [53–55]. Similarly, in sediment tests with the midge C. tentans , sublethal endpoints are often more sensitive than survival as indicators of contaminant stress [9,10,56].…”
Section: Resultsmentioning
confidence: 99%